Identification of Land Degradation and Method of Solution in Zone of Baturagung Hill at Gunung Kidul Regency - Langgeng Wahyu Santosa (Universitas Muhammadiyah Surakarta, 2005)
Baturagung hill is a folded hill range consisting mainly of Tertiary volcanic rocks which have been undergoing severe faulting, jointing and weathering. Lies on the altitude between 200 and 700 meter from see level, the area is characterized by sloping to steep relief with 30% to 40% of slope, and shallow soils with scattered outcrops. Such geomorphological setting has made the area subject to intense soil erosion and masswasthing. Mining activates has also been accounted for the explanation of the current heightened land degradation in the area. The present paper, accordingly, is intended to identify the land degradation by considering mass movement, bare land, and mining activity parameters. The present paper founds that the Baturagung hill can be divided into three zones, namely: (1) the zone of no to low degradation (hill slope and inter-hill valley); (2) the zone of high degradation rate (within the area having 30 40% of slope); and (3) the zone of severe degradation (within the area having slope of more than 45%).